The Late Quaternary Depositional History of the Baram Delta and Its Adjacent Brunei Shelf - Francis Ik Sing Ho (Ikatan Ahli Geologi Indonesia, 2003)
The Baram Delta, located in the NW Borneo, has long been recognized as prolific oil producing province in this region. The stratigraphic history of the Baram Delta has recently become a topic of many studies. The present day Baram Delta depositional processes have been widely used as an analogue to interpret the ancient depositional framework of sedimentary successions in this area. As an aid to the reconstruction of the modern depositional model of the Baram system, this research project is initiated with two main goals.The primary objective of this research is to describe the distribution pattern and acoustic character of the Late Quaternary fluvial-deltaic-estuarine deposits preserved on the western Brunei Shelf. The approach adopted involves the use of high-resolution (Minigun, 2.5 kHz) seismic reflection data to map stratigraphic boundaries and to characterize seismic facies units bounded by these surfaces. Correlation of seismic horizons, mapping of faults and seismic units, and the generation of isochron and paleogeographic maps help to interpret the depositional processes and shelf evolution through the last eustatic cycle.The secondary objective of this research includes the study and evaluation of the evolution of the paleo-Baram coastline during the last highstand, with respect to the present rate of sediment discharge from the Baram River. The result so derived may assist us to better understand the depositional environment of the most recent Baram Delta sequences.